Influences of Extended Family on Intimate Partner Violence: Perceptions of Pakistanis in Pakistan and the United Kingdom - Ali, Parveen Azam; O’Cathain, Alicia; Croot, Elizabeth (Journal of interpersonal violence, 2021)
Limited research has been undertaken on the role of extended family members in Intimate Partner Violence (IPV). This study uniquely explores the perspective of Pakistani men and women about the role of a husband and wife’s families in relation to marital conflict and IPV. For this qualitative study, data were collected through 41 individual interviews, including 20 from Pakistan and 21 from the United Kingdom. The findings are presented in four themes, including “privacy and personal space,” “interference and instigation of problems,” “conflicting and uncommunicated expectations,” and “adjustment facilitation.” A lack of privacy and personal space within a family home shared with extended family on the husband’s side, interference in terms of mothers-in-law and sisters-in-law making complaints about the wife, and the couple’s differing expectations of the husband’s responsibility for his extended family could cause tension and conflict that could lead to IPV. The husband’s family could also have a positive effect by minimizing conflict through offering the couple personal time and helping the wife to adjust to her new family. The wife’s family was perceived as having a much more passive role in terms of not interfering, but instead allowing her to adjust to her new extended family. In conclusion, the husband’s extended family can have a considerable impact on conflict within couples. Public health prevention initiatives for IPV in Pakistani people should address the role of the husband’s extended family. The findings of the study are not only important for the population studied, which is part of an international diaspora, but also for other communities worldwide that value close family structure due to cultural and religious preferences.